Combined modalities for the prevention of ovarian hyperstimulation syndrome following an excessive response to stimulation. (4th March 2018) - Dahan, Michael H.; Tannus, Samer; Seyhan, Ayse; Tan, Seang Lin; Ata, Baris
Abstract: Although the classification and management of ovarian hyperstimulation syndrome (OHSS) are well described in the literature, little attention has been given to modalities that aim to prevent its occurrence. In this retrospective study, we sought to investigate whether a combination of modalities in addition to GnRH agonist triggering in GnRH antagonist cycles could result in better prevention of OHSS. The study included 170 hyperresponder patients who were stimulated with GnRH antagonist protocol and were triggered with GnRH agonist for final oocyte maturation. Freeze all embryos was performed in all patients. The intervention group included treatment with dopamine agonist and restarting the GnRH antagonist. Of the 170 patients included, 63 were included in the intervention group. Compared to no intervention, women in the intervention group were more likely to have: menses within 7 days of the oocyte retrieval, smaller ovarian diameter, the absence of free pelvic fluid, less hemoconcentration and higher serum sodium levels. It can be concluded that combining other modalities in addition to triggering with GnRH agonist in GnRH antagonist cycles, results in targeting several pathways that lead to OHSS and result in rapid resolution of signs of ovarian hyperstimulation.